Lviv in the U.S. Polish Emigrants’ Press after World War II - Chwastyk-Kowalczyk, Jolanta (Respectus Philologicus, 2013)
The article discusses occurrences of topics related to Lviv in Polish opinion-forming newspapers in exile in the United States after World War II. The author followed the New Diaryin the years 1971–1999, together with its appendices, Polish Week (1971–1981) and Polish Review (1981–1999), published in New York. These titles had a wide scope of influence. The analysis of the newspapers’ contents revealed that a small, dispersed community from Lviv, who emigrated to the United States and centered around the Lviv Circle, made their works public regularly in the pages of the New Diary. However, compared with the incidence of the same themes in the Polish emigrants’ press in Western Europe during the same period, it was a marginal phenomenon about accidental topics. The texts mainly focused on unmasking the Soviet authorities’ actions to eliminate traces of Polish culture from Lviv, the devastation of the Lviv Eaglets Cemetery. Additionally, they posted pictures of the Poltva, poems devoted to the city, and anniversary reminiscences of the Lviv defense of 1918. Topics related to Lviv abroad were mostly the domain of its former citizens, who had been forced to leave the city without possibility of return (thanks to the provisions of the Yalta Conference)—journalists, academics, and activists in exile, regularly associated with magazines from the British Isles (the White Eagle, News, Polish Diary, and Soldier’s Diary) as well as Culture from Paris.